DEVELOPMENT OF LOW COST PROJECT BASE LEARNING IN PHYSICS LEARNING OF JUNIOR HIGH SCHOOL - Yennita Yennita; Ruhizan Mohd Yasin; Zanaton Hj Ikhsan (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2017)
The Research have a purpose to create teaching module project base learning basis using science low cost for junior high school student. ADDIE Model (Analysis, Design, Development, Implementation and Evaluation) already chosen for principle module. Learning by project use an application of constructive learning theory and social cognitive theory. Module of low cost project base learning at topic Preassure outcome already passed every step of evolving from ADDIE. All validator agreed every aspect for evaluate the module, such as 1) Modul design 2) All activities 3) Modul content 4) Project Activities 5) Graph/Picture  6) Langguange/Text and 7) Evaluate modul’s content. The experiment using the module as all item for student and teacher already proved to used  the module in every aspect of evaluating. It can be concluded that the module already valid and can be used in bigger scale of learning activities.